Pengaruh manajemen Sumber Daya Manusia Stratejik, manajemen Transformasi dan Perubahan, Manajemen Infrastruktur, Manajemen Kontribusi Terhadap Keunggulan Bersaing dan Kinerja Organisasi (Survei Pada Manajemen S1 Berakreditasi di PTS STIE Kopertis Wilaya - Paramarta, Vip (Business and Management Review, 2011)
The objective of this research was to identify the strategic human resource management, transformation and change management, infrastructure management and contribution management; to identify the magnitude of the influence of strategic human resource management, transformation and change management, infrastructure management and contribution management on the competitive advantage and organizational performance.The methods of the researchare descriptive and explanatory with questionnaire as a primary data collecting tool. The analytic unit in this research is Accredited Management Study Program S1 at Economics College. The subjects in this research are Private Colleges (PTS) opening the Accredited Management Study Program S1 25 of Economics College, Kopertis Region IV, West Java. The data analytic method used descriptive analysis and path analysis.The result  shows that the strategic human resource management, and transformation and change management have no significant influence on the competitive advantage; infrastructure management and contribution management have significant influence on the competitive advantage; the strategic human resource management, transformation and change management, infrastructure management and contribution management have significant influence on the organizational performance; the strategic human resource management, transformation and change management, infrastructure management and contribution management have significant influence on the competitive advantage and organizational performance. Keywords:  Strategic human resource management, transformation and change management, infrastructure management and contribution management, competitive advantage and organizational performance.